Model Teknologi Ai Sebagai Sarana Belajar Percepatan Kecerdasan Emosional Siswa di SDIT Al-Fatih Depok - Nurkaidah Nurkaidah (Ikatan Dai Indonesia, 2026)
This study aims to develop artificial intelligence (AI) technology as a learning tool to accelerate the development of emotional intelligence (EQ) among students at SDIT Al-Fatih Depok. Using a Research and Development (R&D) approach, the study involves needs analysis, system design, development, implementation, and evaluation of an AI-based learning system designed to enhance students' understanding of emotions, stress management, and empathy through interactive simulations. The findings indicate that the application of AI significantly improves students' emotional intelligence and social skills. This innovation is expected to serve as an effective learning model in primary education, supporting the development of non-academic aspects in the digital era.